STUDI KOMPARASI PEMBELAJARAN SENI LUKIS PADA EKSTRAKURIKULER DI SD IT AZ-ZAHRA DAN SD NEGERI BINTORO 04 KABUPATEN DEMAK - Lutfiyah, Ana Rofatul; Rofian, Rofian; Arisyanto, Prasena (JURNAL SINEKTIK, 2020)
This research aims to find out the management management system, administration and extracurricular learning of painting art at SD IT Az-Zahra and SD N Bintoro 04 in encouraging the success of learners in the competition", This type of research is qualitative by presenting descriptive form data. This research uses data collection methods in the form of observations, interviews, questionnaires, and documents. The results of the analysis in this study showed that the management and administration systems at SD IT Az-Zahra and SD N Bintoro 04 found differences such as: school management, financial management system, learning places, participating race activities, and awards given to students. In addition to the differences, there are similarities of learning in the two elementary school, among others: infrastructure, guidance facilities, parental support and learning conducted by SD IT Az-Zahra and SD N Bintoro 04 Demak.